A City for Itself: A Peripheral Mixed City's Struggle for Cultural Capital. (September 2019) - Yavo–Ayalon, Sharon; Aharon–Gutman, Meirav; Alon–Mozes, Tal
Based on the case study of a Fringe theatre festival in a peripheral city in Israel, this article identifies and analyzes a moment of change in power relations between a peripheral city and the country's central city. It offers an alternative perspective to urban discourse, which analyzes art projects in peripheral cities as duplicating colonial relations. We adapted the Marxist concept of a class in itself and a class for itself, from the socioeconomic realm to the urban realm, by using Bourdieu's field theory as a link between the sociology of art and the urban realm. We argue that by taking control over the festival's productive forces, the city evolved from a city in itself to a city for itself . Drawing on ethnographic fieldwork and architectural research, the article analyzes four decades of urban dynamics leading to this change and proposes a theoretical and methodological framework for deciphering contemporary urban process.